AMPHIBIOLOGICAL NOTES I OBSERVATIONS ON SOME AMPHIBIANS OF THE VALLEY OF MEXICO - MALDONADO KOERDELL, MANUEL (Instituto de Salubridad y Enfermedades Tropicales, CD MEXICO, DF, MEX, 1948)
The isolation and detn of the structural formula of the red pigment of the "flor de manita" was described From 950 g of defatted dry powder (1000 blossoms) a glycoside was obtained (930 mg) In the filtrate D-glucose and gallic acid was identified Fr
REV SOC MEX HIST NAT
Keywords: AMPHIBIOLOGICAL NOTES I, OBSERVATIONS, AMPHIBIANS, VALLEY OF MEXICO; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL (ZOOLOGIA); HERPETOLOGIA